Vibrational Communication in Animals - Hill, Peggy S. M. (Harvard University Press, 2022)
In creatures as different as crickets and scorpions, mole rats and elephants, there exists an overlooked channel of communication: signals transmitted as vibrations through a solid substrate. Peggy Hill summarizes a generation of groundbreaking work by scientists around the world on this long understudied form of animal communication. Beginning in the 1970s, Hill explains, powerful computers and listening devices allowed scientists to record and interpret vibrational signals. Whether the medium is the sunbaked savannah or the stem of a plant, vibrations can be passed along from an animal to a potential mate, or intercepted by a predator on the prowl. Vibration appears to be an ancient means of communication, widespread in both invertebrate and vertebrate taxa. Hill synthesizes in this book a flowering of research, field studies documenting vibrational signals in the wild, and the laboratory experiments that answered such questions as what adaptations allowed animals to send and receive signals, how they use signals in different contexts, and how vibration as a channel might have evolved. Vibrational Communication in Animals promises to become a foundational text for the next generation of researchers putting an ear to the ground